IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS INFORMATION COMMUNICATION TECHNOLOGY (ICT) TERHADAP KREATIVITAS BELAJAR SISWA (Studi Kasus Mata Pelajaran Akidah Akhlak di MAN 1 Kota Tasikmlaya) - Wildan, Asep (HASBUNA : Jurnal Pendidikan Islam, 2024)
This study aims to determine the effect of Information Communication Technology (ICT)-based learning models on student learning creativity at MAN 1 Tasikmalaya City. This research was aimed at class X students at MAN 1 Tasikmlaya City with a sample of 84 students. This study uses a survey method using a quantitative approach. The instrument used was a questionnaire using a Likert scale. The analysis technique uses the product moment relationship at a significant level of 5%. The results of the study show that the ICT learning model has a significant influence on students' learning creativity. it can be seen that the correlation number (r) is 0.903. From these figures it can be found that the magnitude of the coefficient of determination shows the influence between the ICT learning model (variable X) on student learning creativity (variable Y) the formula KP = r² x 100%, where (KP is the determining coefficient or determinant and r is the correlation coefficient ) KP = r² x 100% KP = 0.903² x 100% = 81.5%. From the results of these calculations, it can be concluded that learning creativity is influenced by the ICT learning model by 81.5% while the remaining 18.5% is influenced by variables or other factors not examined.Reading results From the results of the t-test it can be discussed the hypothesis proposed as follows, namely the ICT-based learning model has a positive effect on the learning creativity of MAN 1 students in Tasikmlaya City. The results of a simple linear regression analysis show that the ICT-based learning model has tcount (0.903) > ttable (0.220) on learning creativity in MAN 1 Tasikmlaya City.